(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
This article correlated three art pieces of Guatemalan artist Regina José Galindo, whose subjects allude to Efraín Ríos Montt’s dictatorship, with the book Paper Cadavers: The Archives of Dictatorship in Guatemala, by Kirsten Weld. The goal was to investigate performance as a means of survival and/or memory recovery in a prohibitive state. This study analyzed the construction of the archives of the Proyecto para la recuperation del Archivo Histórico de la Policia Nacional (Project for the Recovery of the National Police Historical Archives) from Guatemala, presenting the role of performance for people’s history appropriation and also for the dubious operation of the archives as a source of social memory or as killing machine memory and basis for a coup.